Nitrogen and phosphorus dynamics across an elevational gradient in a Swedish subarctic tundra - Sundqvist, Maja (2011)
Rising temperatures associated with global climate change are likely to drive major shifts in plant and soil properties as well as plant-soil linkages that govern key ecosystem processes in subarctic tundra. However, the tundra landscape is not homogenous, but instead consists of a mosaic of vegetation types which differ greatly in vegetation characteristics and soil fertility. Two types of vegetation commonly co-occur across broad areas of the Fennoscandian subarctic tundra, i.e., heath vegetation dominated by slow-growing dwarf-shrubs and present on N-poor acidic soils, and meadow vegetation, dominated by herbaceous species and present in shallow depressions on more fertile soils. Temperature declines predictably with elevation, and therefore gradients of elevation are powerful natural experiments for studying the effects of long-term changes in temperature on ecosystem properties and processes. This thesis uses an elevational gradient to understand how temperature influences nitrogen (N) and phosphorus (P) dynamics, and how this is associated with shifts in plant and soil microbial properties, for both tundra heath and meadow vegetation. The overall results of this thesis showed that increasing elevation led to an increase in plant limitation of P relative to N, and a general decline in soil P availability but had highly variable effects of soil N availability. Such variation in soil N and P responses to elevation were often associated with the specific characteristics of the plant species that dominated at the different elevations. Importantly, the effect of elevation on aboveground and belowground characteristics differed greatly between tundra heath and meadow vegetation, leading to vastly different responses of litter decomposability, soil microbial properties, soil nutrient cycling, and ultimately N and P availability to elevation among these two vegetation types. In total these findings highlight how shifts in elevation and associated changes in abiotic factors such as temperature not only have ...